Implementation of Strategic Planning in Vocational High Schools to Address the Challenges of the Industrial Revolution 4.0 - Arum Dwi Hastutiningsih; Ian Somosot (Indonesian Journal Of Civil Engineering Education, 2024)
Abstrak: This study examines implementation of strategic planning in Vocational High Schools (SMK). In facing challenges of Industrial Revolution 4.0 the research focuses on 11 principals. Additionally, 22 teachers from SMKs in Special Region of Yogyakarta (DIY) are involved. Utilizing quantitative methodology results reveal intriguing patterns. School principals develop strategic plans. They actively involve teachers. Parents and industry stakeholders participate. A significant emphasis is placed on the use of technology. This enhances effectiveness. Efficiency of SMK management is also improved. Evidence shows integration of digital technologies. Online learning platforms are noted. These are seen in the schools' operations and educational processes. The study highlights the critical role of collaborative and tech-driven approaches. This prepares vocational schools to meet demands of the evolving industrial landscape.Keywords: Strategic Planning, Vocational High Schools, Industrial Revolution 4.0